Microstructured BN composites with internally designed high thermal conductivity paths for 3D electronic packaging - He, Hongying (2022)
Miniaturized and high-power density 3D electronic devices pose new challenges on thermal management. Indeed, prompt heat dissipation in electrically insulating packaging is currently limited by the thermal conductivity achieved by thermal interface materials (TIMs) and by their capability to direct the heat towards heat sinks. Here, we create high thermal conductivity BN-based composites able to conduct heat intentionally towards specific areas by locally orienting magnetically functionalized BN microplatelets using magnetically assisted slip casting (MASC). The obtained thermal conductivity along the direction of alignment is unusually high, up to 12.1 W m-1 K-1 thanks to a high concentration of 62.6 vol% of BN in the composite, a low concentration in polymeric binder and a high degree of alignment. The BN composites have a low density of 1.3 g cm-3, a high stiffness of 442.3 MPa and are electrically insulating. Uniquely, we demonstrate our approach with proof-of-concept composites having locally graded orientations of BN microplatelets to direct the heat away from two vertically stacked heat sources. Rationally designing the microstructure of TIMs to direct heat strategically provides a promising solution for efficient thermal management in 3D integrated electronics.